2020
DOI: 10.2147/rmhp.s240829
|View full text |Cite
|
Sign up to set email alerts
|

<p>Validation of the Ethiopian Version of eHealth Literacy Scale (ET-eHEALS) in a Population with Chronic Disease</p>

Abstract: Background: Although the measurement scale developed by Norman and Skinner is the widely used scale to assess consumers' eHealth literacy, translating and validating the scale for the language of the target population under consideration is necessary. Amharic is the official national language of Ethiopia, with 29.3% of native speakers. Methods: The total sample size calculated was 187 with 6% non-response rate. The internal consistency of the ET-eHEALS was measured using Cronbach's alpha coefficient. Test-rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 36 publications
5
33
0
Order By: Relevance
“…The characteristics of the included eHealth literacy instruments and studies are presented in Multimedia Appendix 2 [ 24 - 64 ]. The eHEALS, which consists of 8 items scored on a 5-point Likert scale, was originally developed in English [ 24 ], and its psychometrics have been studied in diverse languages: Amharic [ 50 ], Mandarin Chinese [ 26 ], Simplified Chinese [ 34 , 36 , 41 ], Dutch [ 25 ], English [ 27 - 30 , 47 , 53 , 54 , 57 , 58 ], German [ 39 , 44 ], Greek [ 48 ], Hebrew [ 45 ], Hungarian [ 37 ], Indonesian [ 43 ], Italian [ 31 , 33 ], Korean [ 32 , 42 , 55 ], Persian [ 38 , 46 ], Polish [ 35 ], Portuguese [ 52 ], Norwegian [ 49 , 56 ], Serbian [ 51 ], and Swedish [ 40 ]. The eHEALS has been used to evaluate diverse populations, including not only youths, adults, and older adults, but also healthy people, patients, caregivers, and health professionals in school, community, and clinic settings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the included eHealth literacy instruments and studies are presented in Multimedia Appendix 2 [ 24 - 64 ]. The eHEALS, which consists of 8 items scored on a 5-point Likert scale, was originally developed in English [ 24 ], and its psychometrics have been studied in diverse languages: Amharic [ 50 ], Mandarin Chinese [ 26 ], Simplified Chinese [ 34 , 36 , 41 ], Dutch [ 25 ], English [ 27 - 30 , 47 , 53 , 54 , 57 , 58 ], German [ 39 , 44 ], Greek [ 48 ], Hebrew [ 45 ], Hungarian [ 37 ], Indonesian [ 43 ], Italian [ 31 , 33 ], Korean [ 32 , 42 , 55 ], Persian [ 38 , 46 ], Polish [ 35 ], Portuguese [ 52 ], Norwegian [ 49 , 56 ], Serbian [ 51 ], and Swedish [ 40 ]. The eHEALS has been used to evaluate diverse populations, including not only youths, adults, and older adults, but also healthy people, patients, caregivers, and health professionals in school, community, and clinic settings.…”
Section: Resultsmentioning
confidence: 99%
“…However, there was inconsistent moderate-quality evidence for convergent validity. The two-factor structure yielded from another 5 studies (IDs 35-39) [ 47 - 50 ] demonstrated insufficient high-quality evidence for structural validity, sufficient high-quality evidence for internal consistency, and sufficient very low-quality evidence for reliability and convergent validity. The three-factor structure of the eHEALS derived from 3 studies (IDs 43-45) [ 54 - 56 ] and a single study ID 47 [ 58 ] demonstrated sufficient high-quality evidence for internal consistency, cross-cultural validity, and known-groups validity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale was originally developed in English (9) and validated in many populations, including adolescents (9)(10)(11) , university students (12) , adults (13)(14)(15) , and the elderly [16][17] This is the main measure used to evaluate digital health literacy, and it is validated in the languages European Portuguese (11) , Spanish (12) , Korean (13) , German (14) , Polish (15), Chinese (18) , Japanese (19) , Italian (20) , Hungarian (21) , Serbian (22) , Amharic (Ethiopia) (23) , Swedish (24) , and Greek (25) . The scale showed good psychometric properties in all these languages.…”
Section: Introductionmentioning
confidence: 99%
“…Skills related to e-Health literacy will enable the patients and empower them to involve in healthcare decision making [18] which will improve patients' health outcomes including quality healthcare [20]. Prior empirical studies have recognized that e-Health literacy is significantly and positively related with patients' health behaviors, knowledge and patients ability to participate in health screening, using mobile technology to accomplish healthcare objectives and goals, research related to healthcare, seeking medical advice among others [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%